A Review of Keyword Spotting as an Audio Mining Technique - Deka, B.K; Das, P (International Journal of Computer Sciences and Engineering, 2019)
Speech is that the essential and therefore the most profitable ways for correspondence between people. Speech is an emerging technology and automatic speech recognition has created advances in recent years. It provides the flexibility to a machine for responding properly to spoken language. Keyword Spotting could be a very important strategy in audio mining that is employed to recover of all occurrences of a given keyword within the knowledge talked expressions. It has transformed into a fascinating and testing zone as the proportion of an audio substance in the web, telephone and diverse sources growing rapidly. It can be viewed as a subproblem of automatic speech recognition where only partial information has got to be extracted from speech utterances. KWS is closely associated with the task of speech transcription and offers several advantages for certain applications. The main aim of this study is to understand the various approaches used for keyword spotting of speech in order that we can find out the methods that provide better accuracy and performance. Additionally, we have quickly examined the Keyword spotting framework and Audio mining system in this paper.